Analysis of Molin River Water Chemistry in the Ordos Basin, China - Hui, Qian; Zhang, Zhihua; Chen, Jie; Zhang, Hanting (Asian Journal of Chemistry, 2013)
Molin river is located in the arid region of Inner Mongolia, China. To study the changes of water composition along the river, 19 river water and groundwater samples were collected for chemical and isotopic analysis. The TDS, major ion concentrations, chemical type, as well as d18O and d2H of river water were compared. Equilibrium speciation calculation was employed to calculate the saturation indices of minerals. Mass balance model was used to analyze the mechanisms of the changes of river water composition. Results showed gypsum dissolution, calcite precipitation, ion exchange, mixing processes and evaporation of river water all play important roles in the formation of river water composition.